2021
DOI: 10.1186/s13244-021-01006-5
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography imaging of septic shock. Beyond the cause: the “CT hypoperfusion complex”. A pictorial essay

Abstract: Septic shock is a medical emergency that represents one of the most important underlying causes for presentation to the Emergency Department. Sepsis is defined as organ dysfunction, life-threatening event caused by a deregulated inflammatory host response to infection, with a mortality risk ranging from 10 to 40%. Early sepsis identification is the cornerstone of management and diagnostic imaging can play a pivotal role in this clinical context. The choice of imaging modality depends on several factors, associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…Patients with sepsis or septic organ failure make up the largest percentage (23 %) and one in three of these patients died. Di Serafina et al emphasize that, even with comparable CT findings, the pathogenic mechanisms of hypotensive shock and septic shock are very different [22]. In general, elevated adrenal density values are associated with activation of the hypothalamic-pituitary-adrenal axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with sepsis or septic organ failure make up the largest percentage (23 %) and one in three of these patients died. Di Serafina et al emphasize that, even with comparable CT findings, the pathogenic mechanisms of hypotensive shock and septic shock are very different [22]. In general, elevated adrenal density values are associated with activation of the hypothalamic-pituitary-adrenal axis.…”
Section: Discussionmentioning
confidence: 99%
“…Die Patienten mit Sepsis oder septischem Organversagen nehmen mit 23 % den größten Anteil ein, wobei jeder dritte dieser Patienten verstarb. Di Serafina et al betonen, dass bei vergleichbaren CT-Befunden die pathogenen Mechanismen, die dem hypotensiven Schock und dem septischen Schock zugrunde liegen, recht unterschiedlich sind [22]. Erhöhte Dichtewerte der Nebennieren werden generell mit einer Aktivierung der Hypophysen-Nebennierenrinden-Achse in Verbindung gebracht.…”
Section: Diskussionunclassified
“…Other factors are associated with NOMI. First, we found that all CT features belonging to the hypoperfusion complex [ 19 , 20 , 23 ], i.e., the hollow adrenal gland sign [ 24 ], organ infarction, flattened inferior vena cava, vasoconstriction of mesenteric vessels [ 5 , 25 27 ] were all associated with NOMI. Indeed, NOMI is the ultimate consequence of prolonged gut hypoperfusion and has a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Not forgetting the countless collateral findings that may be encountered during the CTA examination, a separate mention should be made of the early signs indicative of hypovolaemic shock in severe bleeding states, which fall under the umbrella term of “CT hypoperfusion complex” ( Figure 20 ) [ 20 ].…”
Section: The Diagnostic Role Of Ctamentioning
confidence: 99%